Prosaic conditions : Heinrich Heine and the spaces of Zionist literature - Rokem, Na'ama (Northwestern University Press, 2013)
In this book, the author observes that prose writing -- more than poetry, drama, or other genres -- came to signify a historic rift that resulted in loss and disenchantment. The author treats prose as a signifying practice -- that is, a practice that creates meaning. During the nineteenth and twentieth centuries, prose emerges in competition with other existing practices, specifically, the practice of performance. Using Zionist literature as a test case, the author examines the ways in which Zionist authors put prose to use, both as a concept and as a literary mode. Writing prose enables these authors to grapple with historical, political, and spatial transformations and to understand the interrelatedness of all of these changes.